2022
DOI: 10.3389/fnagi.2022.849443
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Polygenic Risk Score for Late-Onset Alzheimer's Disease With Biomarkers

Abstract: Late-onset Alzheimer's disease (LOAD) is a common irreversible neurodegenerative disease with heterogeneous genetic characteristics. Identifying the biological biomarkers with the potential to predict the conversion from normal controls to LOAD is clinically important for early interventions of LOAD and clinical treatment. The polygenic risk score for LOAD (AD-PRS) has been reported the potential possibility for reliably identifying individuals with risk of developing LOAD recently. To investigate the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…We found that higher N-PRS was associated with increased conversion rate of aMCI. This is consistent with previous findings that PRS for personality was associated with the conversion of aMCI (Li et al, 2022;Lupton et al, 2021). While during a long period of 10-year follow-up, the N-PRS could not predict the conversion of aMCI to AD in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that higher N-PRS was associated with increased conversion rate of aMCI. This is consistent with previous findings that PRS for personality was associated with the conversion of aMCI (Li et al, 2022;Lupton et al, 2021). While during a long period of 10-year follow-up, the N-PRS could not predict the conversion of aMCI to AD in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…With the development of second‐generation genomic sequencing technology, more accurate genomic data can be obtained for more aMCI patients, providing more possibilities for constructing N‐PRS. In clinical practice, the N‐PRS can be employed to distinguish aMCI patients with higher conversion risk of AD, and appropriate interventions for these aMCI patients can prevent or delay their progression to AD (Li et al, 2022 ). We found that higher N‐PRS was associated with increased conversion rate of aMCI.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is an irreversible, progressive, polygenic, neurodegenerative disease that accounts for approximately 70% of dementia cases ( Li et al, 2022 ; Tank et al, 2022 ). The onset of AD is unknown, and nerves undergo pathological changes decades before the onset of symptoms ( Alzheimer’s Association, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identification and immune characteristics of molecular subtypes related to protein glycosylation in Alzheimer's disease Zhaotian Ma 1,2 , Fan Yang 1,3 , Jiajia Fan 1,2 , Xin Li 1,2 , Yuanyuan Liu 1,2 , Wei Chen 1,2 , Honghao Sun 1,2 , Tengfei Ma 1,2 , Qiongying Wang 1,2 , Yueriguli Maihaiti 1,2 and Xiaoqiao Ren 1,2 * Introduction Alzheimer's disease (AD) is an irreversible, progressive, polygenic, neurodegenerative disease that accounts for approximately 70% of dementia cases (Li et al, 2022;Tank et al, 2022). The onset of AD is unknown, and nerves undergo pathological changes decades before the onset of symptoms (Alzheimer's Association, 2021).…”
mentioning
confidence: 99%